Penyuluhan Untuk Meningkatkan Pemenuhan Kebutuhan Dasar Ibu Hamil Untuk Mengurangi Keluhan Nyeri Punggung Pada Pekerja Kerajinan Anyaman - Ni Putu Aryani; Baiq Ricca Afrida; Susilia Idyawati; Sri Hawari Jannati (JPM: Jurnal Pengabdian Masyarakat, 2023)
The need arises as a human effort to survive. In Indonesia, there is no epidemiological data regarding LBP. Sitting for a long time without rest can have an impact on the spinal structure due to the biomechanical processes that occur in the spine. Observations made on several pregnant women who worked as weavers in Batu Mekar Village found that they sat for a long time so that their basic needs were not met. This causes pain in the back. the emphasis is on information through education for someone with a chronic illness so that they have positive thoughts and suggestions about their health condition so that a person's quality of life is good and the expected results are also optimal. The parties involved in this activity were STIKES Yarsi Mataram (lecturers, students), village officials (village head, village secretary), cadres and the community. The method used in this activity is counseling and followed by discussion. Counseling is expected to increase the knowledge of pregnant women to meet the basic needs of pregnant women. Implementation of activities carried out in places that have been agreed with the target participants are pregnant women as many as 30 people. The counseling material provided includes material on meeting the basic needs of pregnant women. The discussion was carried out after the presentation of the material was completed. Participants asked about material that they had not understood about meeting the basic needs of pregnant women. Counseling has proven to be effective in increasing understanding of meeting the basic needs of pregnant women and efforts to prevent back pain, with an increase in score of as much as 30 (from 50 to 80).